Trusted Digital Circuits Hardware Trojan Vulnerabilities, Prevention and Detection - Salmani, Hassan (Springer International Publishing, 2018)
This book describes the integrated circuit supply chain flow and discusses security issues across the flow, which can undermine the trustworthiness of final design. The author discusses and analyzes the complexity of the flow, along with vulnerabilities of digital circuits to malicious modifications (i.e. hardware Trojans) at the register-transfer level, gate level and layout level. Various metrics are discussed to quantify circuit vulnerabilities to hardware Trojans at different levels. Readers are introduced to design techniques for preventing hardware Trojan insertion and to facilitate hardware Trojan detection. Trusted testing is also discussed, enabling design trustworthiness at different steps of the integrated circuit design flow. Coverage also includes hardware Trojans in mixed-signal circuits. Provides a comprehensive vulnerability analysis across the integrated circuits design flow; Introduces security metrics to measure quantitatively the vulnerability of a circuit to hardware Trojan insertion; Describes design techniques to prevent hardware Trojan insertion and to facilitate hardware Trojan detection; Presents testing techniques for trustworthiness at each circuit level.